A cinematographic study of the massive transformation in Cu-Ga alloys - Kittl, Jorge E.; Massalski, T. B. (Pergamon Press Inc., 1966)
Fil: Kittl, Jorge E. Comisión Nacional de Energía Atómica; Argentina